Rasio kalsium fosfor, glukosa darah dan kinerja pertumbuhan ikan Betok (Anabas testudineus) yang diberi prebiotik inulin - Anita Lestari Melinda Siburian; Irawadi Gunawan; Ricky Djauhari (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2020)
The effect of inulin on calcium phosphor ratio, growth performance, survival, and blood glucose level were evaluated on three ponds culture conditions. Each ponds, namely pond A, B and C consists of treatments A3, D1, D3, B1 (pond A); B3, A1, D2, C2 (pond B); and C1, B2, C3, A2 (pond C). Inulin was added onto feed at 0 (A), 1.25 (B), 2.5 (C), and 5.0 g kg feed−1 (D). Bioassays performed with treatments in triplicate, were conducted for 28 days. Feed supplemented with inulin at concentrations 1.25 g kg feed-1 improved calcium phosphor ratio, blood glucose level and growth performance in climbing gouramy fish. The prebiotic inulin increased growth performance and decreased blood glucose level in climbing gouramy fish at concentration of 1.25 g kg feed−1 is a good feed additive. Keywords : Calcium phosphor ratio, blood glucose, growth performance, Anabas testudineus